Disorder-mediated crowd control in an active matter system - Erçağ Pinçe (Nature Portfolio, 2016)
Many living systems, such as bacterial colonies, exhibit collective and dynamic behaviours that are sensitive to the change in environmental conditions. Here, the authors show that a colloidal active matter system switches between gathering and dispersal of individuals in response to a disordered potential.